Activators of Nrf2 to Counteract Neurodegenerative Diseases - Rosa Amoroso; Cristina Maccallini; Ilaria Bellezza (MDPI AG, 2023)
Neurodegenerative diseases are incurable and debilitating conditions that result in progressive degeneration and loss of nerve cells. Oxidative stress has been proposed as one factor that plays a potential role in the pathogenesis of neurodegenerative disorders since neuron cells are particularly vulnerable to oxidative damage. Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is strictly related to anti-inflammatory and antioxidative cell response; therefore, its activation and the consequent enhancement of the related cellular pathways have been proposed as a potential therapeutic approach. Several Nrf2 activators with different mechanisms and diverse structures have been reported, but those applied for neurodisorders are still limited. However, in the very last few years, interesting progress has been made, particularly in enhancing the blood-brain barrier penetration, to make Nrf2 activators effective drugs, and in designing Nrf2-based multitarget-directed ligands to affect multiple pathways involved in the pathology of neurodegenerative diseases. The present review gives an overview of the most representative findings in this research area.